Image Compression Techniques Using Artificial Neural Network - Chandra, Yogesh; Mishra, Shikha (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
This paper contain neural network bases on image compression techniques .The image compression is the application of the data compression on digital images. The main role of the image compression technique which is used to reduce the number of pixels and reduce the broadcast and transmission cost in efficient form and an artificial neural network is a computational structure which is stimulated by observed process in neural network of biological neuron in the brain. Image compression based on back propagation neural network with Liebenberg - marquardt algorithm and it is achieved by image is divided into number of blocks and select the one neural network for each block according to its complexity value. The Training algorithm and back propagation neural network is used to increase the performance and to decrease the convergence time and provide high compression ratio and low distortion. The neural network training process best for image compression and applications.